Metformin use and mortality in Asian, diabetic patients with prostate cancer on androgen deprivation therapy: A population‐based study. Issue 1 (30th September 2022) - Lee, Yan Hiu Athena; Hui, Jeremy Man Ho; Chan, Jeffrey Shi Kai; Liu, Kang; Dee, Edward C.; Ng, Kenrick; Tang, Pias; Tse, Gary; Ng, Chi Fai
Abstract: Background: This study aims to examine the associations between metformin use concurrent with androgen deprivation therapy (ADT) and mortality risks in Asian, diabetic patients with prostate cancer (PCa). Methods: This study identified diabetic adults with PCa receiving any ADT attending public hospitals in Hong Kong between December 1999 and March 2021 retrospectively, with follow‐up until September 2021. Patients with <6 months of medical castration without subsequent bilateral orchidectomy, <6 months of concurrent metformin use and ADT, or missing baseline HbA1c were excluded. Metformin users had ≥180 days of concurrent metformin use and ADT, while non‐users had no concurrent metformin use and ADT or never used metformin. The primary outcome was PCa‐related mortality. The secondary outcome was all‐cause mortality. The study used inverse probability treatment weighting to balance covariates. Results: The analyzed cohort consisted of 1971 patients (1284 metformin users and 687 non‐users; mean age 76.2 ± 7.8 years). Over a mean follow‐up of 4.1 ± 3.2 years, metformin users had significantly lower risks of PCa‐related mortality (weighted hazard ratio [wHR]: 0.49 [95% confidence interval, CI:  0.39–0.61], p  < 0.001) and all‐cause mortality (wHR 0.53 [0.46–0.61], p  < 0.001), independent of diabetic control or status of chronic kidney disease. Such effects appeared stronger in patients with less advanced PCa, which is reflected by the absence of androgen receptor antagonist or chemotherapy use ( p value for interaction: 0.017 for PCa‐related mortality; 0.048 for all‐cause mortality). Conclusions: Metformin use concurrent with ADT was associated with lower risks of mortality in Asian, diabetic patients with PCa.